Book Review: Lucasfilm: Filmmaking, Philosophy, and the Star Wars Universe - Szabó, Helga (AMERICANA E-journal of American Studies in Hungary, 2022)
Lucasfilm: Filmmaking, Philosophy, and the Star Wars Universe Cyrus R. K., Patell New York: Bloomsbury Academic, 2021 280 pages ISBN 9781350100619